Improving Mathematics Learning Result By Applying The Discovery Learning Model And The Utilization of ICT- Based Multimedian - Desy Haryani Handresmawati (Universitas Sebelas Maret, 2020)
The purpose of this study was to improve student learning outcomes in mathematics muple class III elementary school with discovery learning model using ICT-based multimedia. The research conducted was a Classroom Action Research (PTK) in three cycles. In the first cycle, students who completed the evaluation were 52%. In the second cycle, students who completed after evaluating wre 76%. In cycle III the students who completed after carrying out the post test were 94%. These results indicate that the discovery learning model with the use of ICT-based multimedia can improve student learning outcomes, especially Class III mathematics muple at SDN Kedalon 01, Batangan District, Pati Regency.